Choroidal Metastasis from Follicular Cell Thyroid Carcinoma Masquerading as Circumscribed Choroidal Haemangioma. (11th March 2014) - Papastefanou, V. P.; Arora, A. K.; Hungerford, J. L.; Cohen, V. M. L.
Abstract : Choroidal metastases from follicular thyroid carcinoma are uncommon and usually present as an amelanotic lesion against a background of known systemic disease. We present the case of a 56-year-old woman with a thyroid metastatic focus with unusual clinical presentation, systemic involvement, and early response to systemic treatment. A review of the literature accompanies this case presentation.